2019
DOI: 10.1111/jfb.13914
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the biology and seasonal variation in feeding of the east coast round herring Etrumeus wongratanai (Clupeiformes), off Scottburgh, KwaZulu‐Natal, South Africa

Abstract: The basic biology and ecology of the South African east coast round herring Etrumeus wongratanai was investigated from samples of fish collected between 2013 and 2016. This species is short‐lived and reaches a maximum of 3 years of age, with rapid growth in its first year of life. It reproduces from June to December (austral summer) and condition factor was lowest in May through to August and increased from September, probably reflecting the physiological strain before and during spawning. Fish larvae were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In plots of monthly averages, an overall increasing trend was noted from winter to July, which appeared to be followed by an opposite, decreasing trend, especially in females. Similarly, in E. wongratanai off South Africa, the lowest somatic condition was observed between April and August (austral autumn to winter) and the condition increased between September and January (spring to summer) (Vorsatz et al, 2019). In the latter study, high interannual variability was also observed, occasionally masking the usual seasonal pattern.…”
Section: Somatic Conditionmentioning
confidence: 53%
See 2 more Smart Citations
“…In plots of monthly averages, an overall increasing trend was noted from winter to July, which appeared to be followed by an opposite, decreasing trend, especially in females. Similarly, in E. wongratanai off South Africa, the lowest somatic condition was observed between April and August (austral autumn to winter) and the condition increased between September and January (spring to summer) (Vorsatz et al, 2019). In the latter study, high interannual variability was also observed, occasionally masking the usual seasonal pattern.…”
Section: Somatic Conditionmentioning
confidence: 53%
“…Indeed, Osman et al (2013) observed that the diet of E. golanii included high quantities of fish larvae in summer, which these authors attributed to their increased abundance at that time of the year. High consumption of fish larvae in summer has also been reported for E. wongratanai off the east coast of South Africa (Vorsatz et al, 2019).…”
Section: Somatic Conditionmentioning
confidence: 69%
See 1 more Smart Citation
“…Estimates of economic losses in EU Member States are not yet assessed, while further studies are needed to be implemented in order to estimate the abundance of the species in Greek waters and to have sufficient for a holistic and correct assessment (Kourantidou et al, 2022). Until now, it is not known to which extent it functions territorially and competitively with commercial small pelagic species such as the European anchovy and European pilchard (Vorsatz et al, 2019). However, it does not appear to have negative impacts on these stocks and currently no population management practices are in place (Akyol and Ulas, 2016).…”
Section: Magnitude Of Impactsmentioning
confidence: 99%
“…Ecomorphology may be an important indicator of species diet and trophic position (Blasina et al, 2016), being able to identify adaptative convergence in phylogenetically distant species, and adaptative divergences in phylogenetically close ones (Reilly & Wainwright, 1994;Cassati & Castro, 2006). It helps classifying the feeding habits associated with linear models, identifying possible changes in species feeding patterns and trophic levels according to the phase of the life cycle and infer about swimming ability (Vorsatz et al, 2019;Souza & Pompeu, 2020;Podder et al, 2021a,b;Santos et al, 2021).…”
mentioning
confidence: 99%